South west region clinical incidents benchmarking project. Issue 2 (1st September 2011) - Stevens, Alison
Abstract : The Hospice Nurse Managers in the South West have worked collaboratively to develop a tool to monitor clinical incidents within hospice Inpatient units. This tool forms the basis of a quarterly benchmarking exercise. The tool currently in use is based on the national nursing metrics system and consists of an excel spreadsheet detailing numbers of clinical incidents against 1000 bed days including falls, pressure ulcers and medical incidents (Drug errors). Each hospice Nurse manager has an electronic copy of the tool and is responsible for submitting quarterly returns to Dorothy House Hospice Care. The results are then collated and a regional average is produced. Results are shared at SW regional Nurse Manager meetings and possible reasons for variation discussed and good practice examples highlighted. Each hospice has the option to share their individual results and the regional average with their local commissioners or other interested parties. Challenges in setting up the benchmarking system have included ensuring consistency in reporting and the variation in database systems currently in use for data collection/analysis. Benefits have included the opportunity to benchmark against other hospices rather than acute or community providers, the routine of regular discussion with colleagues on how improvements may be made to reduce incidents and demonstration to the Care Quality Commission of a proactive approach to managing clinical incidents. South West Region Forum for Hospice Nurse Managers. March 2011.